Teachers' Perceptions of the Implementation of Inclusive Education Policy at the Junior High School (SMP) Level Regarding the Use of Science Learning Technology in Salatiga City - Cantika Ariani Kusumaningtyas; Tri Astuti (FKIP - Universitas Riau, 2026)
Inclusive education policies in Indonesia mandate equal access to learning for students with special needs, but their implementation in technology-based science learning at the junior high school level remains understudied. This study analyzes the implementation of inclusive education policies regarding the use of science learning technology at SMPN 7 Salatiga the school with the highest number of students with special needs among junior high schools in Salatiga City using the Edward III policy implementation model. This study employed a mixed-methods Exploratory Sequential design, combining semi-structured interviews with confirmatory questionnaires distributed to the school principal, three science teachers, and three Special Education Teachers (GPK). The results indicated that communication and resources were assessed as relatively adequate at the technical level, while the attitudes and organizational structure of the bureaucracy showed greater variation, particularly between the principal and grade-level implementers. The curriculum used remains the standard one and has not been adapted to comply with national regulations mandating curriculum adjustments for students with disabilities. These findings suggest that the success of policy implementation depends more on the individual initiative and adaptability of teachers and GPK than on institutionally structured and coordinated systems, thereby highlighting the need to strengthen evidence-based policies at the school level.